Mapping of QTL associated with resistance to Cassava Brown Streak and Mosaic Diseases in outcrossing cassava cultivars locally cultivated in Tanzania - Masumba, E.; Merwe, A. van der; Myburg, Z.; Kapinga, F.; Kasele, S.; Kulembeka, H.P.; Mkamilo, G.S.; Rounsley, S.; Prochnik, S.E.; Kanju, E.; Ferguson, Morag E. (Plant and Animal Genomes, 2015)
Cassava brown streak (CBSD) and mosaic (CMD) diseases are the major cassava production constraints in the East African region. Efforts to control these diseases were initiated in northeastern Tanganyika in the 1930’s using conventional breeding methods. Despite these efforts, CBSD is spreading, threatening central and western Africa. Identification of molecular markers associated with observed plant resistance and tolerance would facilitate marker assisted breeding leading to efficient breeding, knowledge-based deployment of resistance genes and pre-emptive breeding in West Africa. QTL analysis using a bi-parental F1 mapping population was undertaken to identify QTL for CMD resistance in the variety ‘Albert’ and CBSD resistance in the variety ‘Namikonga’. A one-step genetic linkage map composed of 986 SNP markers and 18 linkage groups spanning 1826.3 cM was generated and used to create a framework map of 242 loci. Phenotyping data was obtained from two disease hotspots in Tanzania from 226 F1 progeny. Significant QTL were identified on chromosomes VIII, XV and I for CMD, CBSD foliar and root symptoms respectively. The maximum LOD score of 19.32 explained variation 34.9% of variation for CMD resistance. CBSD foliar and root symptoms revealed different QTL with moderate LOD scores of up to 5.09 and 7.33, explaining 10.7 and 16.2% respectively of variation. Several other minor significant QTL for all traits were also identified. Genes within QTL regions are being characterized.